ANTITHERMODYNAMICS - Rossler, Otto E. (European Scientific Journal, ESJ, 2013)
â€œAntiâ€ means â€œinsteadâ€ or â€œmirror version ofâ€. The recently introduced new fundamental discipline of cryodynamics can synonymously be called antithermodynanics because it constitutes a mirror-version of thermodynamics. It refers to attractively rather than repulsively interacting many-particle systems. Its predictable influence on the future understanding of physics and the cosmos is outlined by summarizing about 30 references. Novel mathematical results are imminent and decisive technological applications are at the ready.